Interpersonal communication motives used by Malaysian teenagers on flirting via the social media - Salihah Mohd Ali,; Pramela Krish, (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2020)
The medium of communication is rapidly shifting from face-to-face to the faceless communication. Today, people choose to send messages using technology to communicate with their family members, friends, colleagues, or even with strangers. This study focused on text communication via Twitter and the Facebook and it attempts to examine the types of motives in Interpersonal Communication Motives (ICM) used by Malaysian teenagers with particular focus on flirting. This study employed a qualitative approach where the data was collected from tweets and Facebook posts by Malaysian teenagers for a period of five months. This study employed the framework by Rubin, Perse and Barbato (1988) to study the six motives namely pleasure, affection, inclusion, escape, relaxation, and control using content analysis. The study suggests that both genders have specific interpersonal communication motives and their chosen lexical to fulfill their motives for flirting. In analyzing the motives, the choice of words used by these teenagers also plays a role. The data exhibits that both genders were likely use inclusion and pleasure motives for flirting through faceless communication. By using faceless communication through the selected social media, both genders managed to develop their close interpersonal relationships easily by expressing their feelings and less damaging, as they can escape rejection, injury or humiliation if their motives for flirting were not accepted.